3-D characterization of SCC in cold worked stainless steels - Lozano-Perez, S; Saxey, D; Terachi, T; Yamada, T; Cervera-Gontard, L (2009)
Crack initiation and propagation in real materials usually takes place in three dimensions. Conventional characterization techniques are, however, typically restricted to two dimensional observations, making the interpretation of the cracking phenomena a very challenging task. In particular, cold worked stainless steels present an extremely complex interaction between the microstructure, stress and environment which can benefit from this new approach. Several methods to extract 3D information have been applied and discussed; amongst these are FIB slicing, electron tomography and atom probe tomography. 3-D characterization of crack tips has proven an excellent tool for accurately measuring crack opening, understanding 3-D crack morphology and visualizing crystallographic features in the nanometer scale, such as sub-boundaries, deformation bands and oxides.